Right Atrial Pressure Is Associated With Outcomes in Patient With Cardiogenic Shock Receiving Acute Mechanical Circulatory Support - Davila, Carlos D.; Esposito, Michele; Hirst, Colin S.; Morine, Kevin; Jorde, Lena; Newman, Sarah; Paruchuri, Vikram; Whitehead, Evan; Thayer, Katherine L.; Kapur, Navin K. (Frontiers in Cardiovascular Medicine, 2021)
Background: We describe the association between longitudinal hemodynamic changes and clinical outcomes in patients with cardiogenic shock (CS) receiving acute mechanical circulatory support devices (AMCS) at a single center. We hypothesized that improved right atrial pressure is associated with better survival in CS. Methods: Retrospective analysis of patients from Tufts Medical Center that received AMCS for CS. Baseline characteristics and invasive hemodynamics were collected, analyzed, and correlated against outcomes. Hemodynamics were recorded at different time intervals during index admission [pre-AMCS, 24 h after AMCS (post AMCS), and last available set of hemodynamics (final-AMCS)]. Logistic regression was performed to determine variables associated with in-hospital mortality. Results: A total of 76 patients had longitudinal hemodynamics available. In hospital mortality occurred in 46% of the cohort. Mean baseline right atrial pressure (RAP) was significantly higher among non-survivors vs. survivors (19.5+6.6 vs. 16.4+5.3 mmHg). Change in right atrial pressure from baseline to before device removal (ΔRA:final AMCS—pre AMCS) was significantly different between survivors and non survivors (−6.5 ± 6.9 mmHg vs. −2.5 ± 6.2 mmHg p = 0.03). Unadjusted logistic regression revealed baseline RAP (OR: 1.1 95% CI: 1.0–1.2), 24 h post device implant RAP (OR: 1.3 95% CI: 1.1–1.4), and final RAP (OR: 1.3 95% CI: 1.1–1.5) to be significant predictors of in-hospital mortality. In a multivariate logistic regression baseline RAP was no longer significantly associated with mortality in the overall cohort, while 24 h (OR: 1.26 95% CI: 1.1–1.5) and final RAP (OR: 1.3 95% CI: 1.1–1.6) remained statistically significant. Conclusion: We report a novel retrospective analysis of hemodynamic changes in patients with CS receiving AMCS. Our findings identify the potential importance of venous congestion as a prognostic marker of mortality. Furthermore, early decongestion or reduced RA pressure is associated with better survival in these critically ill CS patients. These observations suggest the need for further study in larger retrospective and prospective cohorts of patients with varying degrees of CS severity.